Mechanism of phosphate sensing and signaling revealed by rice SPX1-PHR2 complex structure - Jia Zhou (Nature Portfolio, 2021)
SPX proteins sense phosphate levels in plant cells by binding to inositol polyphosphates (InsP) and suppressing the activity of PHR transcription factors. Here the authors show that when bound to InsP6, the rice SPX1 protein inhibits the activity of PHR2 by attenuating both its dimerization and DNA binding activity.